Efficient Mechanochemical Bifunctional Nanocatalysts for the Conversion of Isoeugenol to Vanillin - Ostovar, Somayeh; Franco, Ana; Puente-Santiago, Alain R.; Pinilla-de Dios, María; Rodríguez-Padrón, Daily; Shaterian, Hamid R.; Luque, Rafael (Frontiers in Chemistry, 2018)
A bifunctional nanocatalyst composed of iron containing SBA-15 material modified with sulfonic acid groups was synthesized by a mechanochemical approach. A full characterization of the obtained nanocatalyst was performed by N2 physisorption isotherms analysis, transmission electron microscopy (TEM), X-ray powder diffraction (XRD) and Fourier-Infrared Spectroscopy (FT-IR). The mechanochemically synthesized nanocatalyst displays a high isoeugenol conversion to vanillin under mild conditions using H2O2 as oxidizing agent. Interestingly, this conversion resulted to be higher than that one obtained with the same material synthesized by an impregnation method. Additionally, the nanocatalyst showed excellent reusability over four successive runs under the studied reaction conditions.